Prescribing Patterns of Drugs in Geriatric Patient - John, Nimmy N; VJ, Arjun; James, Annie; NN, Ramesh; Mahendrakar, Ashok (Journal of Drug Delivery and Therapeutics, 2021)
A prospective observational study on prescribing pattern of drugs in the geriatric patients was conducted in Navodaya Medical College Hospital and Research Centre. The present study aimed to study prescribing patterns of various drugs in elderly patients and to evaluate inappropriate prescribing with the help of beers criteria. A total of 100 patients of geriatric age group(>/65 years) was included in the study for the period of 3 months of which, most of the patients were in the age group of 65-70 years (79.24%), out of which 52 were male and 48 were females. Maximum subjects were prescribed with antibiotics and proton pump inhibitors followed by analgesics. A minimum of 5 drugs were prescribed in 46 cases, followed by 5-8 drugs in 36 cases, then more than 8 drugs were prescribed in around 18 cases. Based on beers criteria 23 patients received potentially inappropriate prescription of at least 1 drug and all these belongs to category A. The study concluded that there is need for careful application of the criteria by health care professional, consumers, payers and health systems should lead to closer monitoring of drug use.Keywords: Prescribing pattern, geriatrics, beers criteria, antibiotics, analgesics.